HUBUNGAN POLA MAKAN DENGAN STATUS GIZI ANAK AUTISM SPECTRUM DISORDER (ASD) KELAS I – VI DI SLB NEGERI SEMARANG TAHUN 2017 - Ulsla Arsil Majidah; Siti Fatimah Pradigdo; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The increasing prevalence of Autism Spectrum Disorder (ASD) children in various countries including Indonesia is inseparable from the emergence of nutritional problems that can affect the nutritional status of ASD children.The aim of this research was to knowing the correlation of eating pattern with nutritional status of ASD children grade I – VI in SLB Negeri Semarang. This type of research is quantitative research using cross sectional approach. The population and the sample in this study were 31 children of ASD selected with purposive sampling method. Data were analyzed using Pearson, Rank Spearman, and Chi-Square tests. The results of this study indicate most children of ASD in overweight (25.8%) and obese (29%). Most history of father (35,5%) and mother's (38,7%) nutritional status were normal. Frequency of food carbohydrate consumptions (48,4%), protein (48,4%), and fat (58,1%) included in “medium” category. The level of consumptions of energy (45,2%), protein (54,8%), and fat (45,2%) at most included in